Becoming atheist: humanism and the secular West - Brown, Callum G. (Bloomsbury Academic, an imprint of Bloomsbury Publishing, Plc, 2017)
Preface -- Acknowledgements -- 1. Introduction -- 2. Narratives of Belief and Unbelief -- 3. The Atheist Child -- 4. The Silent and Indifferent Atheist -- 5. Women, Feminism and Becoming Faithless -- 6. Men, Reason and Radicalism -- 7. Atheism and Ethnicity -- 8. The Humanist Condition -- Sources -- Index.